2017
DOI: 10.1007/s10549-017-4405-3
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-analysis of tumour burden in pre-operative axillary ultrasound positive and negative breast cancer patients

Abstract: BackgroundManagement of the axilla in breast cancer is becoming increasingly conservative. Patients identified with a low axillary nodal burden (two or fewer involved nodes) at sentinel node biopsy (SNB) can avoid completion axillary node clearance (cANC). ‘Fast track’ to ANC in patients with involved nodes on pre-operative ultrasound may be over-treating a subgroup of these patients with low nodal burden, which would have precluded their need for ANC. This systematic review assesses the proportion of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…In case of suspicious ALN, AUS alone or combined with ultrasound-guided needle biopsy is performed for axillary staging to select patients who would benefit from ALND. A recent meta-analysis has shown that the use of AUS in stratifying patients directly to fast-track ALND without SLNB leads to overtreatment in up to two-thirds of patients (32). These data indicated that AUS alone is not sufficiently accurate for axillary staging.…”
Section: P-values Were Calculated By Using χ 2 Test or Wilcoxon Rank-mentioning
confidence: 99%
“…In case of suspicious ALN, AUS alone or combined with ultrasound-guided needle biopsy is performed for axillary staging to select patients who would benefit from ALND. A recent meta-analysis has shown that the use of AUS in stratifying patients directly to fast-track ALND without SLNB leads to overtreatment in up to two-thirds of patients (32). These data indicated that AUS alone is not sufficiently accurate for axillary staging.…”
Section: P-values Were Calculated By Using χ 2 Test or Wilcoxon Rank-mentioning
confidence: 99%
“…Similar findings were observed by Cools et al [27], who reports that patients with ultrasound guided biopsy do not harbor more nodal metastases than who are not subjected to it. Recent meta-analysis by Muneer et al [28] concurred that 43% of patients with positive sentinel lymph node biopsy (SLNB) were subjected to unnecessary ALND.…”
Section: Discussionmentioning
confidence: 99%
“…Fast‐track ALND is based on the concept of higher axillary burden in the clinically non‐palpable (cN0) but ultrasound‐positive axilla. The latest meta‐analysis addressing the issue of axillary burden in patients undergoing ALND after a positive SNB (plus normal ultrasound examination) versus a positive ultrasound examination (and metastasis on histopathology), and which included only studies that applied the clinically relevant threshold of low axillary burden of two or fewer macrometastases, also confirmed the higher axillary nodal burden in the latter group (odds ratio 5·95, 95 per cent c.i. 5·80 to 6·11).…”
mentioning
confidence: 87%
“…This has also recently been demonstrated for subtypes of breast cancer (invasive lobular), where a positive preoperative axillary ultrasound has reported a false‐positive rate of 52 per cent in discriminating between relevant thresholds of axillary burden. The meta‐analysis demonstrated that axillary ultrasonography is not sufficiently specific to identify clinically relevant high nodal burden, and its role in stratifying patients for fast‐track ALND leads to overtreatment in up to two‐thirds of patients. Overtreatment could be avoided simply by directing these patients to SNB without axillary ultrasonography, as was done in the original RCTs of SNB.…”
mentioning
confidence: 91%